2019
DOI: 10.2478/jomb-2018-0010
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miR-210 and miR-1246 as potential biomarkers for differentiating hepatocellular carcinoma from metastatic tumors in the liver

Abstract: Summary Background To date few reports have pointed out the role of circulating miRNAs in discriminating metastatic liver tumors from primary hepatocellular (HCC) tumors. Such discrimination will have significant therapeutic and prognostic implications. The purpose of this study was to evaluate the potential value of a panel of HCC-related circulating miRNAs (miR-142, miR-182, miR-200a, mir-210, miR-211, miR-302b, miR-324, miR-338, miR-340 and miR-1246) as noninvasive biomarkers for discriminating primary HCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 57 publications
0
12
0
1
Order By: Relevance
“…Further molecular characterization has shown that miR-1290 can attenuate apoptosis of primary neurons treated by OGD, although miR-1246 also exhibited similar effect but at a weaker strength as compared with miR-1290. Both miR-1290 and miR-1246 have been implicated in regulating cancer cell proliferation and migration, and exosomal miR-1290 and miR-1246 might serve as tumor biomarkers 5357 . Our data have shown that these two miRNAs are highly enriched in ECs-derived EVs, supporting a neuronal protective role of ECs-derived EVs in stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Further molecular characterization has shown that miR-1290 can attenuate apoptosis of primary neurons treated by OGD, although miR-1246 also exhibited similar effect but at a weaker strength as compared with miR-1290. Both miR-1290 and miR-1246 have been implicated in regulating cancer cell proliferation and migration, and exosomal miR-1290 and miR-1246 might serve as tumor biomarkers 5357 . Our data have shown that these two miRNAs are highly enriched in ECs-derived EVs, supporting a neuronal protective role of ECs-derived EVs in stroke.…”
Section: Discussionmentioning
confidence: 99%
“…High miR-210 expression correlates with poor tumor-free and overall survival of HCC patients [243,245,246]. In addition, miR-210 can be used to discriminate HCC from other metastatic malignancies in the liver [247]. Moreover, miR-210 expression correlates in HCC with elevated tumor stages, vascular invasion and venous metastases indicating that miR-210 could promote metastasis of HCC [216], similarly as described in melanoma.…”
Section: Microrna-210mentioning
confidence: 71%
“…Recent study has demonstrated that miR-210 can be induced by hypoxia-inducible factor 1a (HIF-1a) to express in the tumor microenvironment, which correlates with unfavorable prognosis and greater resistance to chemoradiotherapy in pancreatic cancer (81). Ahmed et al (82). found that serum miR-210 had 73.7% sensitivity and 64.28% specificity in discriminating hepatocellular carcinoma from other metastatic liver cancers, respectively.…”
Section: Discussionmentioning
confidence: 99%